Physician Autonomy and the Opioid Crisis. Issue 2 (June 2018) - Guevremont, Nathan; Barnes, Mark; Haupt, Claudia E.
The scope and severity of the opioid epidemic in the United States has prompted significant legislative intrusion into the patient-physician relationship. These proscriptive regulatory regimes mirror earlier legislation in other politically-charged domains like abortion and gun regulation. We draw on lessons from those contexts to argue that states should consider integrating their responses to the epidemic with existing medical regulatory structures, making physicians partners rather than adversaries in addressing this public health crisis.